How to Enhance Safety of Small Unmanned Aircraft Systems Operations in National Airspace Systems - Dothang Truong; Sang-A Lee; Trong Nguyen (Drones)
The rapid growth of small Unmanned Aircraft Systems (sUASs) has raised some safety concerns when sUASs enter the national airspace. As sUASs interact with traditional manned aircraft within this airspace, guaranteeing their safe operations has emerged as a top priority for aviation authorities, policymakers, and industry stakeholders. To address this challenge, the Federal Aviation Administration (FAA) has introduced waiver rules, empowering operators to navigate deviations from specific regulations under well-defined circumstances. Additionally, the FAA developed proposed rulemakings to seek input on how to enhance safety and address risks associated with sUAS operations. The primary question is: How do these current waiver rules and rulemakings align with the Safety Management System (SMS), and what changes are needed for better alignment? The main purpose of this paper is to compare the FAA’s sUAS safety requirements, particularly waiver rules and rulemakings, with the SMS’s safety risk management component to identify alignments and gaps between them. A qualitative data analysis was conducted using three FAA waiver trend analyses and five Notice of Proposed Rulemakings (NPRMs) for sUASs. The results revealed that most sUAS waiver rules and rulemakings sufficiently align with the first three components of the SRM framework (system analysis, identify hazards, and analyze safety risk). However, there are significant gaps in the last two components (assess safety risk and control safety risk). The findings of this study make significant contributions to the sUAS safety management literature. They enable both the FAA and sUAS organizations to promote uniform operational protocols, training initiatives, and risk mitigation approaches tailored to sUAS operations.